Десакрализация власти и современный политический кризис в Украине - Бурлачук, В. (Социология: теория, методы, маркетинг, 2007)
Under conditions of political crisis in Ukraine the analysis of such concepts, as power,authority, right, law, etc. has assumed a great importance nowadays. It is insufficient to consider the political crisis within legal discourse, because social existence of power is more diverse and complicated than its legal being. Therefore, it is necessary to make a sociological analysis based on the symbolic legitimation concept.